CAPACITY DEVELOPMENT IN REALIZING CHILD-FRIENDLY REGENCY AT THE POPULATION CONTROL,FAMILY PLANNING, WOMAN EMPOWERMENT, AND CHILD PROTECTION AGENCY OF SERDANG BEDAGAI REGENCY - Rizki, Muhammad Farhan; Siahaan, Asima Yanty Sylvania; Ginting, Simson (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
Capacity development is very important in realizing a child-friendly regency because the government can help increase its capacity in designing and implementing its policy and program focused on child prosperity. The indicators of organizational capacity development, proposed by Leavitt indicate some problems in the capacities of physical resource and operational process. Therefore, it is necessary to have organizational capacity development. The objective of the research is to describe and analyse some steps in developing capacity at the Population Control, Family Planning, Woman Empowerment, and Child Protection Agency, Serdang Bedagai Regency, in realizing a Child-Friendly Regency. The research employs qualitative analytic method. The result of the research shows that organizational capacity development needs the dimension of physical resource capacity. Based on organizational structure indicator, a lot of workloads are not balanced by the number of personnel. Consequently, the employees in the section on woman’s protection, child protection, and the fulfilment of child rights sometimes need help from the other sections in carrying out the policy of child-friendly regency/municipality. Based on the finance indicator, it seems that there is no budget allocation which causes some obstacles in some programs of child-friendly regency/municipality. Based in the indicator of regulation, there is no regional regulation concerning child protection which leads to a high violation rate in children.